Degree of paraxiality of a multi-Gaussian beam diffracted by a circular aperture - Cheng, Jinping; Xiao, Yingying; Wu, Hao; Ji, Xiaoling; Wang, Tao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
The degree of paraxiality (DOP) of a diffracted multi-Gaussian beam is discussed. It is shown that the DOP of the multi-Gaussian beam will decrease as it is diffracted by a circular aperture, and the DOP of the diffracted multi-Gaussian beam is influenced by both the aperture radius and the characteristics of beam source. As an example, the dependence of the DOP on the aperture radius, the boundary characteristic, and the beam waist width is investigated.
Optica Applicata, Vol. 53, 2023, nr 4, s. 621-631
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; multi-Gaussian beam; diffraction; degree of paraxiality